INHIBITORY EFFECT OF Cinnamomum zeylanicum OIL EXTRACT ON Aspergillus flavus GROWTH AND AFLATOXIN B1 PRODUCTION - هاشم عبدالكريم; علي وصال; القيسي مهدي (Iraqi Journal of Science, 2024)
The chemical analysis for active groups in oil extract of Cinnamomum zeylanicum was indicated the presence of Glycosides, Alkaloids, Resins, Saponins, Coumarins, Flavonoids, Terpens and Steroids. But the water extract contains Glycosides, Tanins, Resins, Saponins,and phenpls.The oil extract appeared high inhibitory effect on growth and aflatoxin B1 production for Aspergillus flavus locally isolate. The detection of aflatoxin B1 has been done using TLC and HPLC techniques.The total inhibitory effect of oil extract on the growth of A. flavus and aflatoxin B1 production was at the concentrations up to 350ppm using YES medium, while inhibited the growth of the same isolate on PDA medium at the levels up to 650ppm.